Statistical Significance and/or Effect Size? - Štemberger, Tina (Revija za elementarno izobraževanje, 2021)
In the paper, we present some dilemmas concerning the use of statistical significance as the only measure for interpreting results and drawing conclusions. We also introduce effect size measures as a complementary measure in interpretation of the results of statistical tests. We explain the concept of effect size and emphasise the importance of its use in research. We highlight some measures of effect size that we believe could usefully complement the most commonly used statistical test in educational research. We also point out the limitations of using effect size and urge caution in interpreting results.
Keywords: predisposition towards sustainable behaviour, Pre-school Education